Climate Change Risk Disclosures and Stock Market Returns: Empirical Evidence from Nigeria - Aleke, Stephen Friday; IREM, COLLINS OKECHUKWU; ozo, Friday Kennedy; Ogbu , Friday Edeh Ogbu,; Okeke, Frankline C. S. A; Committee, Ekpete (Accounting Department,, 2025)
Purpose — This study aims to examine the effect of climate change risk disclosure on stock market performance in Nigeria from 2006 to 2022 Design/methodology/approach — The study adopted an ex post facto research design and the Vector Error Correction Model (VECM) to estimate the regression coefficients. As the dependent variable, the stock market performance was proxied by the all-share index. In contrast, the climate change policy was proxied by carbon emission taxes (CET) and solid mineral mining taxes (SMT). Other determinant of stock market performance such as the federal government green bond (FGBond) was added to the model to mirror the macroeconomic and financial environment. Findings — From the analysis results, the model test of stationarity showed that all the variables were not stationary at the level but at first difference 1(1). The descriptive and normality tests indicated that the data were normal and fit for the intended analysis. The study found evidence of a long-run relationship among the model variables based on the Johansen test for cointegration. The vector error correction indicated a fast speed of adjustment from the short run to the long run at about 32.04% annually, from the system equation regression. However, the significant findings of the study are: carbon emission taxes had significant positive impact on the stock market performance in Nigeria, (coefficient: LOGCET = 1.085279, p-value 0.0221); solid mineral mining tax has significant positive impact on the stock market performance in Nigeria, (coefficient: LOGSMMT = 0.619464, p-value = 0.0009); and Federal government green bond has significant positive impact on the stock market performance in Nigeria. (Coefficient: LOGFGBond = 0.934925, p-value of 0.0000). Implications—This study's policy implications are that risk mitigation efforts such as carbon emission and solid mineral taxes, as well as green bonds targeting climate change, will remain a practical component of stock market performance policies. Originality/value—Many researchers and policy-makers believe that access to climate change risk mitigation in developing countries improves stock market returns while reducing market vulnerability and contributing to overall economic growth. This approach has expanded rapidly and widely over the past several decades and is currently used in several growing African states. Paper type — Empirical Research